STOCK PRICE REACTIONS TO DIVIDEND ANNOUNCEMENTS OF LISTED COMPANIES ON INDUSTRIALS INDUSTRY GROUP IN THE STOCK EXCHANGE OF THAILAND - กลิ่นชวนชื่น, ชมพูนุช; อัครนุพงศ์, กิตติมา (RMUTT Global Business and Economics Review, 2019)
The objectives of this study are to examine the stock price reactions to dividend announcements (decreasing, unchanging and increasing dividend payment) and to study the factors affecting to the stock price reactions to dividend announcements of listed companies on Industrials Industry group in the Stock Exchange of Thailand. From gathering information, there are one hundred and twelve announcements of the 12-month accounting period dividend payment from thirty-one companies on industrials industry group from 2012 to 2015. The event period for Market Model is 7 days which composes of the date of dividend announcement, three days before and three days after the announcements of dividend payment. The t-test is used for analyzing whether there is the abnormal returns during the dividend announcements period. In addition, it is the test whether size, liquidity and profitability affects to stock prices reaction on dividend announcement. The results show that the announcements on increasing dividend payment from the prior year affects to the stock prices change in the positive way. However, the announcements on decreasing dividend and unchanging dividend payment from the prior year have no effect to the stock prices reaction. Furthermore, the findings also indicate that only profitability (measured by return on equity) affects to the changes in stock prices. Firms with higher return on equity have the cumulative abnormal returns more than those with lower return on equity at the statistically significant level of 0.05. Nevertheless, the results reveal that size and liquidity do not affect to the stock prices reaction on dividend announcements.